SEMANTIC ALTERNATION FROM ANIMAL TO HUMAN UNDER SEMANTIC FIELD PERSPECTIVES - Nguyen Van Tho (Language and Literature Faculty, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2020)
The meanings of words in particular and the linguistic aspects, in general have been studied quite a lot by scientists so far. However, determining the meanings of language units in general and words in particular has proven difficult. The study of meanings of languages has achieved different results. For this reason, research to get into the details still needs to be deeply continued. Besides, ethnic culture is deeply rooted in the subconscious of each member of an ethnic group associated with the language. Because language is a reality of thinking and a means of forming and preserving culture, national thinking and culture are only revealed through speech (language). As a result, language research in terms of cognition and culture is very necessary and urgent in the world at large and Vietnam in particular. The research results show that all words changed their meanings from the animal to the human with regards to semantic field in order to describe the human characteristics of form, personality, etc. When changing their semantic field, these words still brought their original nuances of meaning which combined with the new definitions shaping two socially linguisctic trends - positive and negative. Among them, the number of positive words is only 2 and the negative words are up to 44 cases. Thus, the majority of words were transformed from the animal semantic field to the human one in semantically negative manner. This stems were coined from the cognition about the animals of the Vietnamese people. It is quite interesting to note that whenever Vietnamese people swear profusely, they tend to apply animal-related words, which probably shape a quite special feature of Vietnamese.